PERKUATAN GESER BALOK BETON BERTULANG TAMPANG PERSEGI DENGAN PENAMBAHAN KABEL BAJA (WIRE ROPE) SEBAGAI TULANGAN SENGKANG DAN KOMPOSIT MORTAR - , TIRA ROESDIANA; , Prof. Ir. Iman Satyarno, ME., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The drastic increase of population in Indonesia is also followed by the increase in the need of public facilities and housings. With the demands that the building is damaged should be immediately used agains, it is necessary to the handling of the damage that occured, either by doing repairs or retrofitting. In this research, shear strengthening was done to a rectangular concrete beam by adding wire ropes as reinforcing bars and composite mortars. The use of mortar as a strengthening medium has its own benefit, which is the ease during the casting process due to its high flow nature, thus hopefully solving the problem of dimension limitations and limitations spacing reinforcing bars. While the wire rope was chosen because it has a higher tensile strength than ordinary steel rebars which is expected to enhance the ability of the shear beam. Wire rope also had better mobility than conventional reinforcement so that will make it easier if the retrofitting must be done on multistory buildings with narrow halls. The objective of this research is to know the beamâs shear capacity and ductility, to know the ratio of flexural strength of beam after strengthening, to know the fracture and collapse pattern of the strengthening beam, to evaluate the ease of implementation on the field. Specimens used in this research are two instances of reinforced concrete beam, which consist of 1 strengthening beam with wire rope diameter of 6 mm and length span of 50 mm (BP6) and 1 strengthening beam with wire rope diameter of 8 mm and length span of 100 mm (BP8), each with 250 mm x 350 mm dimension and a length span of 700 mm. The data used for the control beam (BK) were taken from the results of earlier research by Herlina (2009). All the specimens were built in a full scale. The loading method used was a single point static loading. The specimen was placed on a loading frame with simply supported. Parameters measured in this research were the deflection magnitude during the loading process, the magnitude of maximum load, and the resulting fracture pattern. Test results were then compared with the theoretical analysis based on layer method and Response-2000 program. The specimen testing result shows that it can be concluded that BK, BP6 and BP8 maximum loads were 263,4 KN, 690,50 KN, and 671 KN, respectively. By comparing with the control beam (BK), shear strengthening with the addition of wire ropes as reinforcing bars and composite mortar increased the capacity of BP6 and BP8, each by 162,149 % and 154,745 %. BK experienced a collapse shear after the strengthening of BP6 and BP8 experienced a shear failure, because the wire ropes had not reached its optimal condition while the beam already started to break.